Early menopause in patients ooferectimizadas - Gonzáles del Riego, Manuel (2015)
The climacteric syndrome early developed (<2 years) in 41 women castrated before the age of 25, was multisintomático on objectives and organizational aspects, increasing in intensity and frequency in direct relation to the time of castration (<or> 2 years) It is organic signs (osteoporosis and changes in skin and mucous membranes) and late-onset severe. The significant increase in pituitary hormones and sub-normal decline to normal levels of estradiol was early and maintained, while the values of testosterone, prolactin and thyroid hormone unchanged. The treatment with estradiol succinate (8 mg. Per day) was significantly efficient for subjective symptoms and organic inverse relationship of the time kept castration. However, signs such as galactorrhea and skin disorders were resistant to treatment. The pituitary hormone levels and estradiol and progesterone significantly varied without obtaining license to baseline and save the weight of the patient.